Pengaruh RME dalam pembelajaran topik jajargenjang dan belahketupat terhadap kinerja guru dan aktivitas siswa - Bernard Bernard; Ruslan Ruslan; Alimuddin Alimuddin (Seminar Nasional LP2M UNM, 2019)
This study aims to describe the effect of applying the rme approach to teacher performance and student activities in mathematics learning activities. The application of rme is shown through mathematical learning devices developed for pedagogical and divisive topics. The research methods are qualitative and quantitative. A teacher and student of 40 people involved in this study were from the pallangga 5 middle school in gowa regency. to find out the influence shown by applying rme, teacher performance is observed through bridging instruction activities, instructions of main activities, and time, enthusiasm, and situation (tes). Furthermore, for student activities, indicators used solving problems, irrelevant attitude toward learning activities, discussing / asking for other students or teachers, listening teacher's explanation, reading / understanding contextual problems, drawing conclusions about procedure or concept, and delivering ideas / opinion to teacher or students. Overall, the influence provided by implementing the rme in the learning device developed not only provides positive changes to teacher performance but also student activities.